Increasing Understanding of the Sakinah Family Concept in Brides-to-be through the SMART BIMWIN E-Booklet (Study on KUA West Bunguran District) - Hariswati Rachmadani Putri; Dessi Akhriani; M. Imam Badrus Sholeh; Budi Dermawan (Himmah: Jurnal Kajian Islam Kontemporer, 2022)
The purpose of this study was to see an increase in the understanding of the concept of the sakinah family in prospective brides through the preparation of the Smart Bimwin E-booklet at the Office of Religious Affairs in West Bunguran District. The variable that was the target of change in this study was an increase in the understanding of the prospective bride and groom on the concept of a sakinah family through the research method with the One Group Pretest-Posttest Design. In conducting this research, there are stages of material preparation, material preparation, material delivery, and evaluation of the results of material provision. In the evaluation results of the pre-test and post-test after giving the material using the Smart Bimwin Ebooklet media, an increase in understanding of the prospective bride and groom was obtained in the post-test results of 82% from the previous pre-test results of 50%. From these results, the increase rate (N-Gain) was obtained at 0.642% or included in the medium category. Based on the results of this study, it can be concluded that the use of the Smart Bimwin E-booklet as bimwin media can increase understanding of the concept of the sakinah family of prospective brides who carry out premarital marriage guidance at KUA West Bunguran District.Keywords: Understanding Improvement, Sakinah Family Concept, Marriage Guidance, Marriage, Smart Bimwin E-booklet